The Complement System: A Prey of Trypanosoma cruzi - Lidani, Kárita C. F.; Bavia, Lorena; Ambrosio, Altair R.; de Messias-Reason, Iara J. (Frontiers in Microbiology, 2017)
Trypanosoma cruzi is a protozoan parasite known to cause Chagas disease (CD), a neglected sickness that affects around 6-8 million people worldwide. Originally, CD was mainly found in Latin America but more recently, it has been spread to countries in North America, Asia and Europe due the international migration from endemic areas. Thus, at present CD represents an important concern of global public health. Most of individuals that are infected by T. cruzi may remain in asymptomatic form all lifelong, but up to 40% of them will develop cardiomyopathy, digestive mega syndromes, or both. The interaction between the T. cruzi infective forms and host-related immune factors represents a key point for a better understanding of the physiopathology of CD. In this context, the complement, as one of the first line of host defense against infection was shown to play an important role in recognizing T. cruzi metacyclic trypomastigotes and in controlling parasite invasion. The complement consists of at least 35 or more plasma proteins and cell surface receptors/regulators, which can be activated by three pathways: classical (CP), lectin (LP) and alternative (AP). The CP and LP are mainly initiated by immune complexes or pathogen-associated molecular patterns (PAMPs), respectively, whereas AP is spontaneously activated by hydrolysis of C3. Once activated, several relevant complement functions are generated which include opsonization and phagocytosis of particles or microorganisms and cell lysis. An important step during T. cruzi infection is when intracellular trypomastigotes are release to bloodstream where they may be target by complement. Nevertheless, the parasite uses a sequence of events in order to escape from complement-mediated lysis. In fact, several T. cruzi molecules are known to interfere in the initiation of all three pathways and in the assembly of C3 convertase, a key step in the activation of complement. Moreover, T. cruzi promotes secretion of plasma membrane-derived vesicles from host cells, which prevent the activity of C3 convertase C4b2a and thereby may hinder complement. In this review, we aim to present an overview on the strategies used by T. cruzi in order to circumvent the activation of complement and, consequently, its biological effects.